2022
DOI: 10.1155/2022/7074525
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Proprioception and Balance Training Combined with Continuous Nursing on BBS Score and HSS Score of Patients Undergoing Total Knee Arthroplasty

Abstract: Background. Total knee arthroplasty is one of the most effective methods for the treatment of end-stage knee osteoarthritis, but 10% of patients still show insufficient function, strength, and mobility. Continuous nursing service plays an important role in the rehabilitation of patients undergoing total knee arthroplasty. For discharged and convalescent patients, the traditional follow-up model cannot solve the nursing problems of discharged patients. How to meet the health needs of discharged patients under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Fourth, satisfaction with nursing care was significantly higher in the intervention group than in the control group. This finding aligns with that of previous studies that have indicated enhanced satisfaction following postoperative management education for patients with TKA (Lin et al, 2022; Timmers et al, 2019). Twelve weeks after discharge, interventions involving continued app push notifications and exercise feedback may play a beneficial role in ensuring the continuity of nursing care.…”
Section: Discussionsupporting
confidence: 92%
“…Fourth, satisfaction with nursing care was significantly higher in the intervention group than in the control group. This finding aligns with that of previous studies that have indicated enhanced satisfaction following postoperative management education for patients with TKA (Lin et al, 2022; Timmers et al, 2019). Twelve weeks after discharge, interventions involving continued app push notifications and exercise feedback may play a beneficial role in ensuring the continuity of nursing care.…”
Section: Discussionsupporting
confidence: 92%
“…At present, the evaluation of the effect of continuous nursing is mainly focused on the clinical results and the functional assessment of older people [ [39] , [40] , [41] ]. Our results show that continuous nursing not only promoted physical rehabilitation of the hip and knee joints but also played a positive role in daily living ability.…”
Section: Discussionmentioning
confidence: 99%
“…The Hospital for Special Surgery (HSS) 21 scoring system was used to collect HSS knee scores from both groups before surgery and two weeks, three months, and 12 months after surgery to evaluate the functional recovery of the knee joint. The score includes pain (30 points), function (22 points), mobility (18 points), muscle strength (10 points), flexion deformity (10 points), and stability (10 points).…”
Section: Methodsmentioning
confidence: 99%
“…Sample size calculations were based on data from previous studies, 21 and we expected a difference of 85±4.1 between groups in the conventional rehabilitation group at 12 months. At α=0.05, the difference in HSS scores between the quantitative rehabilitation training group and the conventional rehabilitation training group at 12 months postoperatively was tested at approximately 5.2.…”
Section: Methodsmentioning
confidence: 99%